Determinants Of Metabolic Risk In Adolescents: Stress, Dietary Pattern, And Physical Activity - Nisa Dewanti; Dhimas Anggi Septiansyah; Nina Rizka Rohmawati; Mery Angreani Safitri (STIKES Intan Martapura, 2026)
Introduction: The risk of metabolic disease among adolescents has become a public concern, influenced by various behavioral and psychological factors. Objective: This study aims to identify the determinants of metabolic risk among adolescents, focusing on stress, dietary pattern, and physical activity. Methods: A cross-sectional study was conducted on 60 adolescents in one of the high schools in Sidoarjo. Data were collected using a questionnaire and analyzed using the chi-square test and multivariable logistic regression. Results: The results showed that several factors were significantly associated with metabolic risk in the bivariate analysis, namely stress level, diet, physical activity, lifestyle and gender (p < 0.05). However, in the multivariable model, only stress and physical activity remained significant predictors. Adolescents with low physical activity had a significantly higher risk of developing metabolic disease (p = 0.005), while higher stress levels were also associated with an increased risk of developing metabolic disease (p = 0.007). Dietary patterns were not significantly associated after adjustment (p > 0.05). Conclusion: Stress and physical activity are key determinants of metabolic risk among adolescents.